Wacana Jargon “Partai Wong Cilik” Menjelang Kampanye Tahun Politik 2024: Perspektif Hiperrealitas - Elvirida Lady Angel Purba; Wisman Hadi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The purpose of this research is to represent the jargon of the "Partai Wong Cilik" (Party of the Little People) in political discourse leading up to the 2024 political campaign and to examine the forms of hyperreality present in the discourse of the "Partai Wong Cilik" jargon. The research method employed is descriptive with a critical discourse analysis approach by Teun A. van Dijk. The primary data used is derived from discourse texts published on the media platforms kompas.com and detik.com during the period leading up to the political year. Subsequently, the data is analyzed using Van Dijk's critical discourse analysis to examine the representation, symbols and signs, as well as the power used to influence, control, and shape social reality.Discourse is understood as a political context action in the "wong cilik" jargon within the information media. The research results indicate that Van Dijk's Critical Discourse Analysis reveals that the slogan, although directed towards positive representation, also serves as a symbolic power tool used to garner political support. The data shows that behind this identity narrative, there are political motives that emphasize party benefits and power, opening space for critical awareness of political identity dynamics and rhetorical strategies in a dynamic social context. This analysis illustrates that political discourse can create an exaggerated reality, inviting readers to question and seek further understanding related to the complexity and concrete reality and political symbols used.